Lower-extremity running-related injuries among 10,000-meter long distance runners in Ethiopia - Begizew, D. M.; Grace, J. M.; van Heerden, H. J. (Journal of Human Sport & Exercise, 2019)
Despite the popularity and health benefits of running, a popular sporting activity performed by many individuals worldwide, runners are at risk of being injured. Of concern is the lack of evidence-based data and information on Ethiopian 10, 000-meter long-distance runners. The purpose of this study was to establish the incidence and the risk factors associated with lower-extremity running-related injuries amongst 10, 000-meter long distance runners in Ethiopia. A prospective study was used over a period of ten months in eleven running clubs and twelve Youth Athletics Training Programs in Amhara Regional State and Addis Ababa. Participants completed a self-reported questionnaire on 1) demographic characteristics; 2) risk factors associates with running-related injuries and, 3) their injury status. Logistic regression analysis and odds ratio (OR) and its 95% confidence interval (CI) was estimated for the predictor variables. The incidence of running-related injury was 62.4%, corresponding to 0.35 injuries per 100 running hours or 3.54 injuries per 1000 running hours. The most commonly injured anatomical site was the knee (33.6%), with a strain the most common type of injury (36.4%). Participants previously injured had an 8.20 higher OR (2.14-31.40). Runners who train respectively 40km-50km (OR = 0.003, 95% CI, 0.000-0.073) and 50km-60km (OR = 0.053, 95% CI, 0.004-0.728) per week and runners that wore running shoes eight to eleven months (OR = 0.033, 95% CI, 0.003-0.392) was significantly associated with a protective benefit against running-related injuries. Runners, coaches, and medical professionals must acknowledge the specific risk factors associated with running-related injuries. The results underscore urgent interventions to ensure that 10 000-meter Ethiopian long distance runners become injury free.